Biodegradation of di-butyl phthalate (DBP) by a novel endophytic bacterium Bacillus subtilis and its bioaugmentation for removing DBP from vegetation slurry. (15th October 2018) - Huang, Yu-Hong; Huang, Xue-Jing; Chen, Xiao-Hong; Cai, Quan-Ying; Chen, Shaohua; Mo, Ce-Hui; Lü, Huixiong; Wong, Ming-Hung
Abstract: Di-butyl phthalate (DBP) is a widely used plasticizer, recalcitrant and hazardous organic compound with high detection frequencies and concentrations in water and soil that pose a great threat to human health. A novel endphytic bacterium strain N-1 capable of efficiently degrading DBP and utilizing it as sole carbon source was isolated from Ageratum conyzoides. This bacterium was identified as Bacillus subtilis based on its morphological characteristics and 16S rDNA sequence analysis. Under the optimal culture conditions (pH 7.0, 30 °C), degradation percentage of DBP (12.5–100 mg/L) was up to 95% within five days, and its biodegradation half-life was less than 7.23 h. Degradation percentage of high DBP concentration (200 mg/L) was relatively lower (89%) with half-life of 56.8 h. DBP was degraded by Bacillus subtilis N-1 into mono-butyl phthalate and phthalic acid as evidenced by GC-MS analysis. Bioaugmentation of Youngia japonica plant slurry with strain N-1 greatly accelerated DBP dissipation with 97.5% removal percentage (higher by 47% than non-inoculation). The results highlighted that strain N-1 has great potential for bioremediation by plant-endophyte partnerships and for lowering PAE accumulation in crops. Graphical abstract: Image Highlights: A novel endphytic Bacillus subtilis N-1 capable of degrading DBP was isolated. Intermediates without accumulation revealed DBP complete degradation pathway. Bioaugmentation with strain N-1 resulted in DBP efficient removal from plant slurry.